Instructional Supervision and Teacher Performance Improvement: A Multiple-Case Study of Islamic Secondary Schools - Kasiman, Kasiman; Patimah, Siti; Murtafiah, Nurul Hidayati (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Academic supervision is a central component of instructional leadership, yet empirical understanding of how supervision is operationalized as a developmental and value-based practice in Islamic secondary schools remains limited. This study examines how madrasah principals plan, implement, evaluate, and follow up academic supervision to improve teacher performance in Madrasah Tsanawiyah in Metro City, Indonesia. Using a qualitative multiple-case study design, data were collected from three madrasahs through semi-structured interviews, non-participant observations, and document analysis. Informants were selected purposively based on their direct involvement in supervision practices, while data were analyzed thematically through within-case and cross-case comparisons. The findings reveal that effective supervision operates as a cyclical process consisting of systematic planning, classroom observation, formative feedback, evaluation, mentoring, and continuous professional development. These practices supported improvements in teachers’ lesson planning, classroom management, instructional delivery, assessment practices, and reflective professionalism. The study also found that principal commitment, teacher openness, collaborative culture, and the availability of supervision instruments strengthened supervisory effectiveness, whereas limited time, administrative workload, scheduling conflicts, and insufficient technical training constrained its implementation. This study contributes a process-oriented and culturally grounded model of instructional supervision that integrates instructional leadership, clinical supervision, school improvement, and Islamic ethical values. The findings imply that madrasahs should institutionalize structured supervision systems, strengthen principals’ instructional leadership capacity, and embed follow-up coaching into continuous teacher professional development.